Does international capital flow lead to a housing boom? A time-varying evidence from China. Issue 7 (3rd October 2017) - Su, Chi Wei; Wang, Zhi-Feng; Nian, Rui; Zhao, Yanping
ABSTRACT: This paper examines the causal relationship between the housing prices ( HP ) and the international capital flows ( ICF ) in China. With structural changes existing, we find that long-run relationship using full-sample data is unstable, suggesting that traditional Granger causality test is not reliable. However, we further find an unstable short-run relationship between ICF and HP when assessing the stability of the parameters and there are bidirectional causal relationships between ICF and HP for several sub-periods. Additionally, our findings indicate both positive and negative bidirectional causal relations between the series. Based on the arbitrage of ICF, the results suggest that the rise of Chinese HP is the underlying force for the inflows of international capital. Meanwhile, a surge in capital inflows may be accompanied by a rise in the price of housing. This confirms the theoretical analysis that there is an interconnected transmission mechanism between the ICF and the HP, which is diverse and depends both on the flow of ICF and on other factors.